Ethnomedicinal plants used by the Malayali tribes of Bodamalai Hills, Eastern Ghats, Tamil Nadu, India - Nigesh, S.; Vijayakumar, K. K.; Mahendran, S. (Journal of Phytology, 2025)
Ethnomedicinal plants have played a vital role for human healthcare systems across the world. Ethnomedicinal research is necessary to investigate different biological resources for usage as remedies. Many traditional medicinal herbs have been utilized extensively by indigenous people of India to treat a variety of human and animal-related illnesses. The current ethnobotanical investigation was conducted in the Bodamalai Hills of the Eastern Ghats, Tamil Nadu, India. The study revealed that the Malayali tribes of Bodamalai Hills used 55 plants from 45 genera and 28 families to treat various diseases such as abdominal pain, arthritis, asthma, bone disorders, blood disorders, bronchitis, cancer, cardiovascular diseases, cholera, cold, cough, fever, constipation, cuts, wounds, diabetes, diarrhoea, dysentery, ear problems, elephantiasis, fertility problems, jaundice, malaria, nervous disorders, paralysis, piles, skin diseases, smallpox, stomach disorders, toothaches, tuberculosis, ulcers, and urinary disorders. The tribes still rely on medicinal plants. The research findings showed that the number of traditional medicinal healers is declining since younger tribes have begun to migrate to towns and cities and lack interest in and expertise in this type of medicine. Therefore, documentation is required in order to properly conserve the ethnomedicinal plants.